2023
DOI: 10.1200/jco.22.00970
|View full text |Cite
|
Sign up to set email alerts
|

Sequencing of Androgen-Deprivation Therapy of Short Duration With Radiotherapy for Nonmetastatic Prostate Cancer (SANDSTORM): A Pooled Analysis of 12 Randomized Trials

Abstract: PURPOSE The sequencing of androgen-deprivation therapy (ADT) with radiotherapy (RT) may affect outcomes for prostate cancer in an RT-field size-dependent manner. Herein, we investigate the impact of ADT sequencing for men receiving ADT with prostate-only RT (PORT) or whole-pelvis RT (WPRT). MATERIALS AND METHODS Individual patient data from 12 randomized trials that included patients receiving neoadjuvant/concurrent or concurrent/adjuvant short-term ADT (4-6 months) with RT for localized disease were obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In a recent pooled analysis of 12 studies of short-term ADT comparing neoadjuvant/concurrent with concurrent/adjuvant, the authors found that concurrent/adjuvant ADT should be the standard of care when short-term ADT is indicated in combination with RT. 10 In another meta-analysis that compared short with longer ADT duration combined with RT, prolonging the proportion of ADT that follows RT up to 1.5–3 years but not neoadjuvant ADT was associated with improved MFS, regardless of risk group, age, and RT dose delivered. 11…”
Section: Discussionmentioning
confidence: 99%
“…In a recent pooled analysis of 12 studies of short-term ADT comparing neoadjuvant/concurrent with concurrent/adjuvant, the authors found that concurrent/adjuvant ADT should be the standard of care when short-term ADT is indicated in combination with RT. 10 In another meta-analysis that compared short with longer ADT duration combined with RT, prolonging the proportion of ADT that follows RT up to 1.5–3 years but not neoadjuvant ADT was associated with improved MFS, regardless of risk group, age, and RT dose delivered. 11…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in prostate size under ADT measured in this study was within the range of other published studies [ 27 , 28 , 29 ]. The timing of starting ADT before or concurrently with radiotherapy is controversial for oncological efficacy [ 30 , 31 ]. However, waiting for the prostate to shrink after a few months of ADT contributes to relief of the organs at risk and to lower toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…
We thank Abner and Vicini 1 for their correspondence in response to our article. 2 We agree that those performing meta-analyses and pooled analyses must take measures to account for important limitations inherent to evaluating heterogeneous data sets. However, we disagree with several of the statements made by Abner et al, such as ascribing potential survival benefits observed in this analysis to substantial progress in the delivery of radiation therapy.
…”
mentioning
confidence: 90%
“…That study was not subject to the forms of bias implied by the authors, given it was purely based on randomized evidence from ADT sequencing. The fact that two randomized trials from two different countries, 3-5 a pooled analysis of the two trials, 6 and the SANDSTORM meta-analysis 2 all numerically or significantly favored adjuvant ADT in the setting of PORT lends strong credence to the validity of this effect. None showed any potential benefit of neoadjuvant ADT with PORT.…”
mentioning
confidence: 97%